Increase of compliance with methods of body therapy - Anyshchenko, Олена (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the increase of compliance with methods of body therapy.